Invisible Stanley - Brown, Jeff, 1926-2003; Nash, Scott, 1959- (New York : Scholastic, 2009)
One morning after a thunderstorm, the Lambchop family is surprised to discover that Stanley is suddenly invisible.
H
b
b
Keywords: Brothers -- Fiction; Humorous stories